Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Certainly! Let's solve the problem step-by-step to find the original point whose reflection over the line [tex]\( y = -x \)[/tex] results in the point [tex]\((-4, 9)\)[/tex].
The rule [tex]\( r_{y = -x}(x, y) \)[/tex] tells us how to transform a point [tex]\((x, y)\)[/tex] by reflecting it across the line [tex]\( y = -x \)[/tex]. This means that if you have a point [tex]\((x, y)\)[/tex], after reflection, it will become [tex]\((-y, -x)\)[/tex].
We are given the image of the reflected point as [tex]\((-4, 9)\)[/tex]. We need to determine the original point [tex]\((x, y)\)[/tex] before it was reflected.
1. Start with the reflection rule: [tex]\( r_{y = -x}(x, y) \rightarrow (-y, -x) \)[/tex].
2. According to the problem, after applying the reflection rule, the coordinates of the image are [tex]\((-4, 9)\)[/tex]. Therefore, we set up the following equations based on the rule:
[tex]\[ -y = -4 \quad \text{and} \quad -x = 9 \][/tex]
3. Solve the equations for [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:
[tex]\[ -y = -4 \implies y = 4 \][/tex]
[tex]\[ -x = 9 \implies x = -9 \][/tex]
4. Thus, the original point before reflection is [tex]\((9, -4)\)[/tex].
To summarize, by reflecting the point [tex]\((9, -4)\)[/tex] across the line [tex]\( y = -x \)[/tex], we get the point [tex]\((-4, 9)\)[/tex]. Therefore, the original point whose image is [tex]\((-4, 9)\)[/tex] after reflection is:
[tex]\[ (9, -4) \][/tex]
The correct answer is: [tex]\((9, -4)\)[/tex].
The rule [tex]\( r_{y = -x}(x, y) \)[/tex] tells us how to transform a point [tex]\((x, y)\)[/tex] by reflecting it across the line [tex]\( y = -x \)[/tex]. This means that if you have a point [tex]\((x, y)\)[/tex], after reflection, it will become [tex]\((-y, -x)\)[/tex].
We are given the image of the reflected point as [tex]\((-4, 9)\)[/tex]. We need to determine the original point [tex]\((x, y)\)[/tex] before it was reflected.
1. Start with the reflection rule: [tex]\( r_{y = -x}(x, y) \rightarrow (-y, -x) \)[/tex].
2. According to the problem, after applying the reflection rule, the coordinates of the image are [tex]\((-4, 9)\)[/tex]. Therefore, we set up the following equations based on the rule:
[tex]\[ -y = -4 \quad \text{and} \quad -x = 9 \][/tex]
3. Solve the equations for [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:
[tex]\[ -y = -4 \implies y = 4 \][/tex]
[tex]\[ -x = 9 \implies x = -9 \][/tex]
4. Thus, the original point before reflection is [tex]\((9, -4)\)[/tex].
To summarize, by reflecting the point [tex]\((9, -4)\)[/tex] across the line [tex]\( y = -x \)[/tex], we get the point [tex]\((-4, 9)\)[/tex]. Therefore, the original point whose image is [tex]\((-4, 9)\)[/tex] after reflection is:
[tex]\[ (9, -4) \][/tex]
The correct answer is: [tex]\((9, -4)\)[/tex].
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.